A caprolactam hydrofinishing catalyst and a method for preparing the same

CN122912833APending Publication Date: 2026-10-16江苏华海三联净化材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202610992406.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-06
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]目前国内己内酰胺加氢精制催化剂主要有以下几种:(1)晶态雷尼镍催化剂:主要分为粉末雷尼镍(5-100um)和颗粒状雷尼镍(2-10mm),其中粉末雷尼镍催化剂在釜式反应器中使用,生产工艺较为复杂,操作繁琐,催化剂分离耗时且催化剂消耗量大

Benefits of technology

(1)所述载体为所述氧化铝和所述氧化铬的复合氧化物,且加入了稀土金属和过渡金属为助剂,形成了以稳固的铬-铝固溶体为主体骨架,稀土金属和过渡金属的氧化物富集在铬-铝骨架颗粒的表面、孔道内壁及晶界处。铬-铝固溶体骨架提供了内在热稳定性,晶界富集的稀土金属氧化物像“晶界钉扎剂”,强力抑制载体在反应温度下的晶粒长大,从而保证了载体在长周期运行中能保持高比表面积和孔道结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912833A_ABST
    Figure CN122912833A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of catalyst, in particular to a catalyst for low-temperature organic sulfur conversion of synthesis gas and a preparation method thereof.The present application adopts the technical scheme that the content of nickel oxide is 20-30% by weight percentage, the content of molybdenum oxide is 3-10%, the content of chromium oxide is 2-10%, the content of aluminum oxide is 45-75%, and the content of the additive is 1-5%, the specific surface area is 180-260 m2 / g, the pore volume is 0.45-0.65 cm3 / g, the bulk density is 0.65-0.75 g / ml, the strength is 180-210 N / cm, and the supported catalyst is prepared by using the coprecipitation-impregnation method. 3 The present application has the advantages that the catalyst has high activity and good structural stability, can resist the erosion of caprolactam aqueous solution for a long time, and can achieve the effect of caprolactam refining by using the fixed bed process under relatively mild and wide operating conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, and in particular to a catalyst for the hydrogenation and refining of caprolactam and its preparation method. Background Technology

[0002] China is the world's largest producer and consumer of caprolactam (CPL). By 2025, China's production capacity will account for more than 65% of the global total. As an important organic chemical raw material, caprolactam is mainly used to produce nylon-6 chips, which are then processed into nylon fibers, engineering plastics and films. These materials are widely used in textiles, automotive parts, electronics, aerospace, daily necessities manufacturing and pharmaceuticals.

[0003] The production processes for caprolactam include cyclohexane oxidation, hydroxylamine, and phenol methods. Currently, the mainstream industrial production method used in the market is the cyclohexanone ammonium oxime process. First, cyclohexane is produced by hydrogenating benzene. Cyclohexane is then oxidized to cyclohexanone, which is then ammonium-oximeized to obtain cyclohexanone oxime. This oxime is then subjected to the Beckmann rearrangement to obtain crude caprolactam, which is further refined to obtain caprolactam. However, the crude caprolactam contains a small amount of unsaturated impurities with similar molecular structures and boiling points to caprolactam. These impurities cannot be removed by conventional distillation, and they can cause yellowing and decreased polymer thermal stability during the subsequent nylon-6 polymerization process, severely affecting product grade and value.

[0004] Hydrogenation refining of caprolactam involves introducing hydrogen gas into a crude caprolactam solution under the action of a special catalyst. This selectively hydrogenates unsaturated impurities, converting them into saturated compounds, which can then be effectively separated and removed through subsequent distillation processes, resulting in high-quality caprolactam products.

[0005] At present, the main types of catalysts for the hydrogenation refining of caprolactam in China are as follows: (1) Crystalline Raney nickel catalyst: mainly divided into powdered Raney nickel (5-100um) and granular Raney nickel (2-10mm). Among them, powdered Raney nickel catalyst is used in a batch reactor, which has a relatively complex production process, cumbersome operation, time-consuming catalyst separation and large catalyst consumption. Granular Raney nickel is used in fixed-bed reactors. Due to its small specific surface area of ​​only 10-100㎡ / g, it reacts under alkaline conditions. As the catalyst channels are used, the activity is easily blocked, leading to a decrease or even deactivation, resulting in a short service life. (2) Amorphous alloy catalyst: used in magnetically stabilized bed reactors, with nickel as the main active component. Due to the presence of a uniform magnetic field in the reactor, the magnetic amorphous alloy catalyst exists stably in the reactor and does not flow with the reaction liquid. It can fully contact the reaction liquid and react. However, the process is relatively complicated, labor intensity is high, and online catalyst separation is difficult. (3) Noble metal catalyst: used in fixed-bed reactors, with activated carbon or modified alumina as the carrier and palladium as the active component. The catalyst has high activity and good selectivity. The process is continuous and simple, but the catalyst cost is high. (4) Supported nickel catalyst: The supported catalyst, which uses low-cost metallic nickel as the active component and is supported on modified alumina with high strength and large specific surface area, is used in a fixed bed reactor. The process is simple to operate, but it requires high catalyst strength. Moreover, the purity of caprolactam after hydrogenation is often low and cannot meet the high quality requirements.

[0006] Patent CN109453780A discloses a catalyst for the hydrogenation refining of caprolactam, which uses coconut shell activated carbon as a carrier and is treated with nitrogen-containing compounds, and then supported with one or more of Ni, Cu, Ce, and Co. The catalyst of this invention has strong acid and alkali resistance, and can withstand temperatures up to 80℃ and 8.25h. -1 Under process conditions of 0.8 MPa, a relatively good hydrogenation effect was achieved. The PAN value of the feed liquid was 12, which decreased to 2-4 after hydrogenation. However, this method requires the use of a specially treated carrier, the preparation process is complicated, and the binding force between the active component and the activated carbon is insufficient, which poses a risk of nickel loss in the liquid phase environment.

[0007] CN102050783a discloses a catalyst, which involves mixing and pulping a mixture of SiO2-coated iron-containing magnetic microparticles, aluminum sol or TiO2 sol, and nano-CaCO3, followed by spray drying and granulation to prepare 50-70 μm spherical catalyst supports. A 1% Pd / support catalyst is then prepared using an impregnation method. The catalyst is then tested in a magnetically stabilized bed reactor at 100 °C, 1.2 MPa, and for 30 h. -1 Under reaction conditions of a hydrogen-to-liquid ratio of 6, the PM value of caprolactam products can reach 730s. This method uses the precious metal Pd, which is costly.

[0008] CN103086968a discloses a fixed-bed hydrogenation refining method for caprolactam that uses a supported nickel or noble metal palladium catalyst at 1.0 MPa and 5 h⁻¹. -1 Hydrogenation under liquid space velocity (LSH) conditions with PM values ​​above 1500s is ineffective, and the final product's PM value does not meet the general market technical requirement of PM values ​​above 20000s.

[0009] CN106140195a discloses a method for hydrogenating caprolactam using a particulate Raney nickel catalyst in a fixed bed at 80 °C, 0.75 MPa, and 2.0 h⁻¹. -1 At liquid hourly space velocities (LHSVs), caprolactam products achieve PM values ​​exceeding 30,000 s. However, due to the sponge-like porous structure of the outer surface layer of Raney nickel, this catalyst is prone to dissolution and deactivation or catalyst bed collapse after prolonged use under alkaline conditions.

[0010] Chinese patent CN112221504a discloses a method for preparing a catalyst for the hydrogenation refining of caprolactam, the catalyst itself, and a method for refining caprolactam using the same. The catalyst uses nickel as the active component and the support is a nano-alumina or alumina-silica composite with numerous mesoporous structures. The catalyst is prepared by an impregnation-deposition precipitation method. The prepared powder is then calcined and extruded into clover-shaped strips or sheeted into cylindrical shapes. The catalyst preparation process is relatively complex and requires the preparation of catalyst powder for reshaping, resulting in a low pore volume of the catalyst. The calcined catalyst powder has poor colloidal solubility, resulting in poor strength of the finished catalyst, which is not suitable for industrial applications. Furthermore, the catalyst performance evaluation conditions are not disclosed.

[0011] In summary, current catalysts for caprolactam hydrorefining generally employ powdered or granular Raney nickel catalysts, or supported catalysts with nickel or precious metals as the main active components. Regardless of whether a batch reactor, magnetically stabilized bed reactor, or fixed bed reactor is used, the PM value of caprolactam after hydrorefining generally does not exceed 20,000s, which is significantly lower than the PM value requirement of greater than 30,000s for superior caprolactam. Furthermore, existing supported catalysts have poor strength, are prone to pulverization, and have a short industrial service life.

[0012] Therefore, it is necessary to develop a new catalyst for the hydrogenation refining of caprolactam, its preparation method, and its application to solve the aforementioned problems existing in the current technology. Summary of the Invention

[0013] The purpose of this invention is to provide a caprolactam hydrogenation refining catalyst applicable to fixed-bed reactors, its preparation method and application. The catalyst is required to have high activity, good structural stability, and be able to withstand the erosion of caprolactam aqueous solution for a long time. Under relatively mild and wide operating conditions, the fixed-bed process can achieve the effect of caprolactam refining, and the refined caprolactam can reach the superior grade (PM value above 30,000).

[0014] The technical solution of the present invention is as follows: A catalyst for the hydrogenation refining of caprolactam, characterized in that, by weight percentage, the content of nickel oxide is 20-30%, the content of molybdenum oxide is 3-10%, the content of chromium oxide is 2-10%, the content of alumina is 45-75%, the content of the auxiliary agent is 1-5%, the specific surface area is 180-260 m² / g, and the pore volume is 0.45-0.65 cm³. 3 The hydrogenation refining catalyst, with a bulk density of 0.65–0.75 g / ml and a strength of 180–210 N / cm, is a supported catalyst prepared by a co-precipitation-impregnation method and applied in a fixed-bed reactor. The supported catalyst consists of a support, an active component, and an auxiliary agent. The support includes alumina and chromium oxide, the active component includes nickel oxide and molybdenum oxide, and the auxiliary agent includes one or two rare earth metals and transition metals.

[0015] Furthermore, the rare earth metal is one or both of lanthanum and cerium; the transition metal is one or both of titanium and zirconium.

[0016] A method for preparing a caprolactam hydrogenation refining catalyst, characterized by the following steps: S0: providing a first mixture containing aluminum and chromium, a second mixture containing an additive, and a third mixture containing nickel and molybdenum; S1: dissolving a precipitant to prepare a solution, then adding the first and second mixtures to the precipitant solution in a co-current dripping manner and stirring to obtain a uniform precipitate. The pH value is strictly controlled during the co-current dripping process. After precipitation is complete, stirring is stopped and aging begins. After aging, the mixture is filtered, washed, dried, and calcined to obtain a modified catalyst powder. After adding molding aids and pore-forming agents to the catalyst powder, it is kneaded, extruded, dried, and calcined to obtain a modified catalyst support; S2: impregnating the thoroughly dissolved third mixture onto the molded catalyst support, aging it at room temperature for 3-5 hours, drying it at 100-130 degrees Celsius for 4-6 hours, and finally calcining it at 300-500 degrees Celsius for 4-6 hours to obtain the caprolactam hydrogenation refining catalyst.

[0017] Further, the step of co-precipitating the first mixture and the second mixture to obtain a catalyst support containing an auxiliary agent includes: S11: completely dissolving the precipitant to prepare a solution of a certain concentration, then slowly adding the first mixture and the second mixture to the precipitant solution by parallel dripping and stirring the reaction, strictly controlling the solution pH to 7-9 during the dripping process; S12: after the two mixtures have been added and precipitation is complete, stopping the stirring and starting aging for 4-8 hours, after aging, filtering and washing the precipitate with deionized water with a conductivity of <5 μS / cm, stopping the washing when the conductivity of the washed water is <100 μS / cm, drying the solid precipitate at 100-120℃ for 2-6 hours to obtain a composite basic salt precursor, and then calcining it at 500-800℃ in air for 4-6 hours. S13: The catalyst powder is kneaded with binder, plasticizer, pore-forming agent, etc. in a certain proportion and then extruded into a clover-shaped catalyst carrier with a diameter of φ1.5mm*(3~8)mm. After drying at 100~120℃ for 4~6 hours to ensure that the moisture content of the carrier is <3%, the modified catalyst carrier is then calcined at 700~900℃ for 3~6 hours to obtain the modified catalyst carrier.

[0018] Furthermore, the precipitant is one or more of ammonium carbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, and potassium bicarbonate.

[0019] An application of a caprolactam hydrogenation refining catalyst is characterized by its use in a fixed-bed reactor for the hydrogenation refining of caprolactam. The fixed-bed reactor is packed with the caprolactam hydrogenation refining catalyst, and a hydrogen gas and crude caprolactam solution with a specific hydrogen-to-liquid ratio are simultaneously introduced for hydrogenation refining. The caprolactam constitutes 25-55% of the solution by mass, the molar ratio of hydrogen gas to the caprolactam aqueous solution is (2-4):1, the hydrogenation refining temperature is 50-70°C, the hydrogenation refining pressure is 0.5-1.0 MPa, and the volume hourly space velocity (VHSV) is 1-3 h⁻¹. -1 .

[0020] The beneficial effects of this invention are: (1) The carrier is a composite oxide of alumina and chromium oxide, with rare earth metals and transition metals added as additives, forming a stable chromium-aluminum solid solution as the main framework. Oxides of rare earth metals and transition metals are enriched on the surface of the chromium-aluminum framework particles, the inner walls of the channels, and the grain boundaries. The chromium-aluminum solid solution framework provides intrinsic thermal stability, and the rare earth metal oxides enriched at the grain boundaries act as "grain boundary pinning agents," strongly inhibiting grain growth of the carrier at the reaction temperature, thereby ensuring that the carrier can maintain a high specific surface area and channel structure during long-term operation.

[0021] (2) Caprolactam purification requires moderate acidity to activate impurity molecules, but excessive acidity can lead to side reactions of caprolactam itself. Chromium in the support provides necessary and moderately strong L acid sites for adsorbing and activating impurity molecules containing nitrogen, oxygen, etc. The rare earth metals on the surface of the support are alkaline, which neutralizes some of the strong acid sites, avoiding excessive adsorption and side reactions of caprolactam on the strong acid sites, thereby greatly improving the selectivity of the hydrogenation target product.

[0022] (3) The highly dispersed rare earth metal and transition metal nanoparticles on the surface of the support create a large number of heterogeneous interfaces and defects. These sites are excellent sites for anchoring Ni and Mo active species, which can effectively prevent the migration and aggregation of active metals during drying and calcination, ensuring the extremely high Ni-Mo active phase dispersion of the caprolactam hydrogenation refining catalyst and the high catalyst activity.

[0023] (4) The strong anchoring effect of the support on Ni and Mo makes it difficult for the active metal to be lost under the scouring of the reaction medium. The catalyst has good stability, and the moderate acid and alkali environment on the surface of the support can effectively adsorb, transform or repel certain impurities that cause catalyst poisoning, thus giving the catalyst a certain ability to resist poisoning and carbon deposition, thereby extending the service life of the catalyst.

[0024] (5) The hydrogenation refining catalyst of caprolactam has high hydrogenation activity and good selectivity. The hydrogenated caprolactam has high purity and low color. The PM value (potassium permanganate value) of the hydrogenated caprolactam reaches more than 30,000s. Attached Figure Description

[0025] Figure 1 Comparative evaluation results of PM values ​​for A2 and B3 after 1500 hours of operation; Figure 2 The comparison and evaluation results of the PAN values ​​of A2 and B3 after 1500 hours of operation; Figure 3 The physical properties and content composition of catalysts A1-A6 and B1-B3 are provided. Figure 4 Evaluation results of the hydrogenation purification of caprolactam using catalysts A1-A6 and B1-B3; Figure 5 A comparison of the strengths of catalysts A2 and B3; Detailed Implementation

[0026] In existing caprolactam catalysts and related patent literature, some catalyst supports contain silica. Silica is weakly acidic, which is beneficial for improving the dispersion of active metals and promoting the reaction of acidic sites, but it can lead to side reactions of caprolactam, resulting in poor product quality. Other catalysts have poor alkali resistance and structural stability, leading to problems such as easy loss of active metals, collapse of pore structure, and short catalyst life with use. Still other catalysts have poor activity and low conversion rate of unsaturated impurities, resulting in substandard caprolactam quality.

[0027] To address the aforementioned technical problems, embodiments of the present invention provide a caprolactam hydrogenation refining catalyst, comprising an active component, a support, and an auxiliary agent; the active component comprises nickel oxide and molybdenum oxide, the support comprises aluminum oxide and chromium oxide, and the auxiliary agent comprises rare earth metals and transition metals.

[0028] Based on the weight percentage of the caprolactam hydrogenation refining catalyst, the content of nickel oxide is 20-30%, the content of molybdenum oxide is 3-10%, the content of chromium oxide is 2-10%, the content of alumina is 45-75%, and the content of the auxiliary agent is 1-5%. The specific surface area of ​​the caprolactam hydrogenation refining catalyst is 180-260 m² / g, and the pore volume is 0.45-0.65 cm³. 3The catalyst has a bulk density of 0.65–0.75 g / ml and a strength of 180–210 N / cm. The caprolactam hydrogenation refining catalyst comprises a support, an auxiliary agent, and an active component. The support comprises alumina and chromium oxide, the auxiliary agent comprises one or two rare earth metals and transition metals, and the active component comprises nickel oxide and molybdenum oxide. The alumina and chromium oxide interact to form a composite support. The abundant, high-strength L-acid sites on the surface act as strong anchoring sites (strong SMSI effect), generating a strong chemical reaction with the metal precursor. This results in extremely high dispersion of the active metals (such as Ni and Mo), forming smaller and more uniform nanoparticles. The addition of chromium oxide significantly improves the alumina lattice energy, greatly enhancing its resistance to sintering. This allows the support to maintain a stable high specific surface area and pore structure under harsh conditions. Furthermore, the strong acid sites help to promptly convert or vaporize the carbonized precursor, preventing pore blockage and coverage of active sites. This significantly improves the hydrogenation stability of the caprolactam hydrogenation refining catalyst and extends its lifespan. The additive not only prevents alumina grain migration and growth, effectively inhibiting the phase transformation of γ-Al₂O₃ at high temperatures, but also forms a physical barrier or interface layer between Ni / Mo particles and the Al₂O₃ support, preventing direct contact between the active metal particles and the support, thereby significantly slowing down the Ni / Mo phase transition. The surface migration and aggregation of atoms inhibit the formation of harmful nickel aluminate spinels, and the intervention of transition metals can change the surface properties of Al2O3, providing a large number of new anchoring sites, which helps the dispersion of active precursors during calcination and obtains smaller and more uniformly distributed Ni and Mo particles after reduction, thereby improving catalyst activity. Based on the weight percentage of the caprolactam hydrorefining catalyst, the content of nickel oxide is 20-30%, the content of molybdenum oxide is 3-10%, the content of chromium oxide is 2-10%, the content of alumina is 45-75%, and the content of the additive is 1-5%. Too low or too high a content of the active metal components will affect the hydrogenation activity, selectivity, and cost of the caprolactam hydrorefining catalyst; the content of the support alumina, chromium oxide, and additives will directly affect the structural stability, dispersibility, and other indicators of the caprolactam hydrorefining catalyst. The present invention is illustrated below with specific embodiments, but the scope of protection of the present invention is not limited to the provided embodiments.

[0029] In some embodiments of the present invention, a method for preparing a caprolactam hydrogenation refining catalyst is provided, characterized in that the preparation method includes the following steps: S0: Provides a first mixture containing aluminum and chromium, a second mixture containing additives, and a third mixture containing nickel and molybdenum.

[0030] S1: Dissolve the precipitant to prepare a solution. Then, add the first and second mixtures to the precipitant solution in a co-current dripping manner and stir to obtain a uniform precipitate. Strictly control the pH value during the co-current dripping process. After precipitation is complete, stop stirring and begin aging. After aging, filter and wash, then dry and calcine to obtain modified catalyst powder. Add molding aids and pore-forming agents to the catalyst powder, then knead, extrude, dry, and calcine to obtain a modified catalyst carrier.

[0031] S2: The thoroughly dissolved third mixture is impregnated onto the catalyst support after the above molding treatment, aged at room temperature for 3 to 5 hours, dried at 100 to 130 degrees Celsius for 4 to 6 hours, and finally calcined at 300 to 500 degrees Celsius for 4 to 6 hours to obtain the caprolactam hydrogenation refining catalyst.

[0032] In some embodiments of the present invention, the first mixture comprises aluminum nitrate and chromium nitrate.

[0033] In some embodiments of the present invention, the first mixture comprises aluminum nitrate and ammonium dichromate.

[0034] In some embodiments of the present invention, the first mixture comprises chromium-containing pseudoboehmite.

[0035] In some embodiments of the present invention, the rare earth metal precursor in the additive includes one or two of lanthanum nitrate and cerium nitrate.

[0036] In some embodiments of the present invention, the transition metal precursor in the additive includes one or two of titanium nitrate, zirconium oxynitrate, and others.

[0037] In some embodiments of the present invention, the third mixture comprises nickel nitrate and ammonium molybdate.

[0038] In some embodiments of the present invention, the third mixture comprises nickel acetate and ammonium molybdate.

[0039] In some embodiments of the present invention, the precipitant is one or more of ammonium carbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, and potassium bicarbonate.

[0040] In some embodiments of the present invention, in order to prevent the second mixture from prematurely hydrolyzing and precipitating during the co-precipitation process, a complexing agent needs to be added in advance. The complexing agent is one or more of citric acid, tartaric acid, and EDTA.

[0041] In some embodiments of the present invention, the active components are fully impregnated onto the support during the catalyst preparation process. In order to prevent problems such as loss of active components or poor dispersion of active components that may occur due to excessive impregnation in one step, a multi-step impregnation method (two or three impregnations) can be adopted.

[0042] In some embodiments of the present invention, the temperature at which the first mixture and the second mixture are added dropwise in parallel to cause a co-precipitation reaction is 50–70°C, preferably 50–60°C.

[0043] In some embodiments of the present invention, the step of co-precipitating the first mixture and the second mixture to obtain the catalyst support containing the auxiliary agent includes: S11: Dissolve the precipitant completely to prepare a solution of a certain concentration, and then slowly add the first mixture and the second mixture to the precipitant solution by parallel dripping and stirring. During the dripping process, strictly control the pH of the solution to 7-9.

[0044] S12: After the two mixed solutions have been added dropwise and precipitation is complete, stop stirring and begin aging for 4–8 hours. After aging, filter and wash the precipitate with deionized water with a conductivity of <5 μS / cm. Stop washing when the conductivity of the effluent is <100 μS / cm. Dry the solid precipitate at 100–120°C for 2–6 hours to obtain the composite basic salt precursor. Then, calcine it at 500–800°C in air for 4–6 hours to obtain the modified catalyst powder.

[0045] S13: The catalyst powder, binder, plasticizer, pore-forming agent, etc. are kneaded together in a certain proportion and then extruded into strips. The strips are extruded into clover-shaped catalyst supports with a diameter of φ1.5mm*(3~8)mm. The supports are then dried at 100~120℃ for 4~6 hours to ensure that the moisture content of the supports is <3%. Finally, the supports are calcined at 700~900℃ for 3~6 hours to obtain modified catalyst supports.

[0046] In some embodiments of the present invention, in order to provide interparticle bonding force, the binder may be one or more selected from nitric acid, acetic acid, kaolin, starch, guar gum, and hydroxypropyl methylcellulose.

[0047] In some embodiments of the present invention, in order to reduce the friction between the powder and the mold, improve plasticity, and prevent the extrusion strip from cracking, the plasticizer may be one or more selected from glycerol, polyethylene glycol, stearic acid, and guar gum.

[0048] In some embodiments of the present invention, in order to control the pore volume and pore size distribution of the carrier, the pore-forming agent may be selected from one or more of starch, cellulose powder, polymethyl methacrylate, and graphite powder.

[0049] In some embodiments of the present invention, in order to wet the powder and form a plastic paste, the wetting agent may be selected from deionized water, ethanol, and methanol, with deionized water being preferred.

[0050] In some embodiments of the present invention, an application of the caprolactam hydrogenation refining catalyst is also provided. This catalyst is used in a fixed-bed reactor for the hydrogenation refining of caprolactam. The fixed-bed reactor is packed with the caprolactam hydrogenation refining catalyst, and a hydrogen gas and crude caprolactam solution with a certain hydrogen-to-liquid ratio are simultaneously introduced for hydrogenation refining. The caprolactam accounts for 25-55% of the solution by mass, the molar ratio of hydrogen gas to the caprolactam aqueous solution is (2-4):1, the hydrogenation refining temperature is 50-70°C, the hydrogenation refining pressure is 0.5-1.0 MPa, and the volume hourly space velocity is 1-3 h⁻¹. -1 . Example 1

[0051] A first mixture containing aluminum nitrate and chromium nitrate, a second mixture containing lanthanum nitrate and titanium nitrate with added complexing agent citric acid, and a third mixture containing nickel nitrate and ammonium molybdate are provided. Potassium carbonate, the precipitant, is completely dissolved to prepare a solution of a certain concentration. The first and second mixtures are then slowly added to the precipitant solution in a parallel-flow dropping manner, with stirring maintained at 55°C. The pH of the solution is strictly controlled between 7 and 9 during the dropping process. After both mixtures have been added and precipitation is complete, stirring is stopped, and aging begins for 5 hours. After aging, the precipitate is washed with deionized water with a conductivity <5 μS / cm. Washing is stopped when the conductivity of the washed water is <100 μS / cm. The solid precipitate is dried at 120°C for 4 hours to obtain a composite basic salt precursor, which is then calcined at 550°C for 4 hours in air to obtain modified catalyst powder. The catalyst powder, along with guar gum powder, polymethyl methacrylate, nitric acid, and water, were kneaded in a certain proportion and extruded into strips. These strips were then shaped into clover-shaped catalyst supports with a diameter of φ1.5mm * (3-8)mm. The supports were then dried at 120℃ for 4 hours to ensure a moisture content <3%, and finally calcined at 800℃ for 5 hours to obtain a modified catalyst support. The thoroughly dissolved third mixture containing nickel nitrate and molybdenum nitrate was impregnated onto the above-treated catalyst support. The mixture was first aged at room temperature for 5 hours, then dried at 120℃ for 4 hours, and finally calcined at 350℃ for 4 hours to obtain catalyst A1. Based on the weight percentage of catalyst A1, the content of nickel oxide was 29.1%, molybdenum oxide was 3.5%, chromium oxide was 3.2%, aluminum oxide was 62.1%, lanthanum oxide was 0.9%, and titanium oxide was 1.2%. Example 2

[0052] A first mixture containing aluminum nitrate and ammonium dichromate, a second mixture containing lanthanum nitrate and zirconium oxynitrate with added complexing agent citric acid, and a third mixture containing nickel acetate and ammonium molybdate are provided. Potassium carbonate, the precipitant, is completely dissolved to prepare a solution of a certain concentration. The first and second mixtures are then slowly added to the precipitant solution via a parallel-flow dripping method, with stirring maintained at 55°C. The pH of the solution is strictly controlled between 7 and 9 during the dripping process. After both mixtures have been added and precipitation is complete, stirring is stopped, and aging begins for 5 hours. After aging, the precipitate is washed with deionized water with a conductivity <5 μS / cm. Washing is stopped when the conductivity of the washed water is <100 μS / cm. The solid precipitate is dried at 120°C for 4 hours to obtain a composite basic salt precursor, which is then calcined at 500°C for 4 hours in air to obtain modified catalyst powder. The catalyst powder, along with guar gum powder, polymethyl methacrylate, nitric acid, and water, were kneaded in a certain proportion and extruded into strips. These strips were then shaped into clover-shaped catalyst supports with a diameter of φ1.5mm * (3-8)mm. The supports were then dried at 120℃ for 5 hours to ensure a moisture content of <3%, and finally calcined at 800℃ for 5 hours to obtain a modified catalyst support. The thoroughly dissolved third mixture containing nickel nitrate and molybdenum nitrate was impregnated onto the above-treated catalyst support. The mixture was first aged at room temperature for 5 hours, then dried at 120℃ for 4 hours, and finally calcined at 300℃ for 5 hours to obtain catalyst A2. Based on the weight percentage of catalyst A2, the content of nickel oxide was 27.1%, molybdenum oxide was 4.3%, chromium oxide was 3.5%, aluminum oxide was 61.9%, lanthanum oxide was 1.2%, and zirconium oxide was 2.0%. Example 3

[0053] A first mixture containing aluminum nitrate and ammonium dichromate, a second mixture containing cerium nitrate and titanium nitrate with added complexing agent citric acid, and a third mixture containing nickel nitrate and ammonium molybdate are provided. Potassium carbonate, the precipitant, is completely dissolved to prepare a solution of a certain concentration. The first and second mixtures are then slowly added to the precipitant solution in a parallel-flow dropping manner, with stirring maintained at 55°C. The pH of the solution is strictly controlled between 7 and 9 during the dropping process. After both mixtures have been added and precipitation is complete, stirring is stopped, and aging begins for 5 hours. After aging, the precipitate is washed with deionized water with a conductivity <5 μS / cm. Washing is stopped when the conductivity of the washed water is <100 μS / cm. The solid precipitate is dried at 120°C for 4 hours to obtain a composite basic salt precursor, which is then calcined at 550°C in air for 4 hours to obtain modified catalyst powder. The catalyst powder, along with guar gum powder, polymethyl methacrylate, nitric acid, and water, were kneaded in a certain proportion and extruded into clover-shaped catalyst supports with a diameter of φ1.5mm * (3-8)mm. These supports were then dried at 120℃ for 5 hours to ensure a moisture content of <3%, and finally calcined at 850℃ for 4 hours to obtain a modified catalyst support. The thoroughly dissolved third mixture containing nickel nitrate and molybdenum nitrate was impregnated onto the above-treated catalyst support. The mixture was first aged at room temperature for 5 hours, then dried at 120℃ for 4 hours, and finally calcined at 350℃ for 4 hours to obtain catalyst A3. Based on the weight percentage of catalyst A3, the content of nickel oxide was 28.3%, molybdenum oxide was 3.8%, chromium oxide was 4.1%, aluminum oxide was 61.0%, cerium oxide was 1.1%, and titanium oxide was 1.7%. Example 4

[0054] A first mixture containing aluminum nitrate and chromium nitrate, a second mixture containing cerium nitrate and zirconium oxynitrate with added complexing agent citric acid, and a third mixture containing nickel acetate and ammonium molybdate are provided. Potassium carbonate, the precipitant, is completely dissolved to prepare a solution of a certain concentration. The first and second mixtures are then slowly added to the precipitant solution via a parallel-flow dripping method, with stirring maintained at 55°C. The pH of the solution is strictly controlled between 7 and 9 during the dripping process. After both mixtures have been added and precipitation is complete, stirring is stopped, and aging begins for 5 hours. After aging, the precipitate is washed with deionized water with a conductivity <5 μS / cm. Washing is stopped when the conductivity of the washed water is <100 μS / cm. The solid precipitate is dried at 120°C for 4 hours to obtain a composite basic salt precursor, which is then calcined at 550°C for 4 hours in air to obtain modified catalyst powder. The catalyst powder, along with guar gum powder, polymethyl methacrylate, nitric acid, and water, were kneaded in a certain proportion and extruded into strips. These strips were then shaped into clover-shaped catalyst supports with a diameter of φ1.5mm * (3-8)mm. The supports were then dried at 120℃ for 5 hours to ensure a moisture content of <3%, and finally calcined at 900℃ for 3 hours to obtain a modified catalyst support. The thoroughly dissolved third mixture containing nickel nitrate and molybdenum nitrate was impregnated onto the above-treated catalyst support. The mixture was first aged at room temperature for 4 hours, then dried at 120℃ for 4 hours, and finally calcined at 350℃ for 4 hours to obtain catalyst A4. Based on the weight percentage of catalyst A4, the content of nickel oxide was 27.9%, molybdenum oxide was 3.6%, chromium oxide was 3.8%, aluminum oxide was 61.5%, cerium oxide was 1.3%, and zirconium oxide was 1.9%. Example 5

[0055] A chromium-containing boehmite mixture, a second mixture of lanthanum nitrate and zirconium oxynitrate with added complexing agent citric acid, and a third mixture containing nickel nitrate and ammonium molybdate are provided. The chromium-containing boehmite mixture, guar gum powder, polymethyl methacrylate, nitric acid, and water are mixed, kneaded, and extruded into strips. The mixture is first dried at 120°C for 4 hours, then calcined at 800°C for 4 hours to obtain a catalyst support. The second mixture containing lanthanum nitrate and zirconium oxynitrate is impregnated onto the catalyst support, then aged at room temperature for 4 hours, dried at 120°C for 4 hours, and finally calcined at 350°C for 4 hours to obtain a catalyst intermediate containing lanthanum and zirconium as auxiliary agents. The third mixture containing nickel nitrate and ammonium molybdate is impregnated onto the catalyst intermediate containing lanthanum and zirconium as auxiliary agents, then aged at room temperature for 4 hours, dried at 120°C for 4 hours, and finally calcined at 380°C for 4 hours. Catalyst A5 was obtained after hours. It contained 25.6% nickel oxide, 3.4% molybdenum oxide, 4.8% chromium oxide, 64.1% aluminum oxide, 0.7% lanthanum oxide, and 1.4% zirconium oxide. Example 6

[0056] A chromium-containing boehmite mixture, a second mixture of lanthanum nitrate and titanium nitrate with added complexing agent citric acid, and a third mixture containing nickel nitrate and ammonium molybdate are provided. The chromium-containing boehmite mixture, guar gum powder, polymethyl methacrylate, nitric acid, and water are mixed, kneaded, and extruded into strips. The mixture is first dried at 120°C for 4 hours, then calcined at 850°C for 4 hours to obtain a catalyst support. The second mixture containing lanthanum nitrate and titanium nitrate is impregnated onto the catalyst support, then aged at room temperature for 4 hours, dried at 120°C for 4 hours, and finally calcined at 350°C for 4 hours to obtain a catalyst intermediate containing lanthanum and titanium as auxiliary agents. The third mixture containing nickel nitrate and ammonium molybdate is impregnated onto the catalyst intermediate containing lanthanum and titanium as auxiliary agents, then aged at room temperature for 4 hours, dried at 120°C for 4 hours, and finally calcined at 380°C for 4 hours to obtain catalyst A6. The content of nickel oxide is 25.3%, the content of molybdenum oxide is 3.1%, the content of chromium oxide is 4.5%, the content of aluminum oxide is 64.7%, the content of lanthanum oxide is 0.8%, and the content of titanium oxide is 1.6%.

[0057] Comparative Example 1 The preparation method of catalyst B1 is the same as in Example 1. Based on the mass percentage of the catalyst B1, the content of nickel oxide is 20%, the content of molybdenum oxide is 3.5%, the content of chromium oxide is 3.2%, the content of aluminum oxide is 71.2%, the content of lanthanum oxide is 0.9%, and the content of zirconium oxide is 1.2%.

[0058] Comparative Example 2 The preparation method of catalyst B2 is the same as in Example 2. The support is composed of alumina and silicon oxide. Based on the mass percentage of the catalyst B2, the content of nickel oxide is 27.1%, the content of molybdenum oxide is 4.3%, the content of silicon oxide is 3.5%, the content of alumina is 61.9%, the content of lanthanum oxide is 1.2%, and the content of zirconium oxide is 2.0%.

[0059] Comparative Example 3 Catalyst B3 was prepared according to the method described in Example 5 of CN202011259627.0, and by mass percentage of the catalyst B3, the content of nickel oxide was 25%, the content of lanthanum oxide was 1.5%, the content of zirconium oxide was 2.0%, the content of silicon oxide was 3.5%, and the content of aluminum oxide was 68%.

[0060] The content composition and physical property data of the catalysts in Examples 1-6 and Comparative Examples 1-3 are shown in the figure. Figure 3 (Physical properties and content composition of catalysts A1-A6 and B1-B3).

[0061] Catalyst evaluation experiment Catalyst reduction: The caprolactam hydrogenation refining catalyst is loaded into a fixed-bed reactor. Nitrogen gas is first introduced to replace the air in the fixed-bed reactor, and then hydrogen gas is introduced to reduce the catalyst. The hydrogen flow rate is gradually increased with the reduction reaction, and the reaction temperature is also gradually increased. After hydrogen reduction at a temperature of 350-450℃ for 10-20 hours until the active metal component is completely reduced, the catalyst can be used for caprolactam hydrogenation refining.

[0062] Hydrogenation purification of caprolactam: A certain flow rate of hydrogen gas and crude caprolactam solution is introduced into a fixed-bed reactor packed with the caprolactam hydrogenation purification catalyst. The molar ratio of hydrogen gas to crude caprolactam solution is (2-4):1. The mass percentage of caprolactam in the aqueous solution is 25-55%. The hydrogenation purification reaction temperature is 50-70℃, the hydrogenation purification reaction pressure is 0.5-1.0 MPa, and the volume hourly space velocity is 1-3 h⁻¹. -1 . Specific Implementation Example 1

[0063] Hydrogen gas and crude caprolactam solution were introduced into a fixed-bed reactor containing the caprolactam hydrogenation refining catalyst. The catalyst loading volume was 100 ml, the molar ratio of hydrogen gas to crude caprolactam solution was 2.5:1, the caprolactam content in the aqueous solution was 30% by mass, the PAN value of the caprolactam aqueous solution was 25, the PM value was 600S, the hydrogenation refining reaction temperature was 55°C, the hydrogenation refining reaction pressure was 0.7 MPa, and the volume hourly space velocity was 2 h⁻¹. -1 The results of hydrogenating the caprolactam solution with catalysts A1-A6 and B1-B3 are shown in the figure. Figure 4 (Evaluation results of hydrogenation refining caprolactam using catalysts A1-A6 and B1-B3).

[0064] from Figure 4 The data show that, under the required reaction conditions, the caprolactam hydrogenation purification catalyst of the present invention produces caprolactam with a PAN value of <1.0, a PM value of >30000S, and high purity after hydrogenation purification. Specific Implementation Example 2

[0065] Hydrogen gas and crude caprolactam solution were introduced into fixed-bed reactors respectively packed with caprolactam hydrogenation refining catalysts A2 and B3. The loading volume of catalysts A2 and B3 was 100 ml each. The molar ratio of hydrogen gas to crude caprolactam solution was 2.5:1. The mass percentage of caprolactam in the aqueous solution was 30%. The PAN value of the caprolactam aqueous solution was 25, and the PM value was 600S. The hydrogenation refining reaction temperature was 55°C, the hydrogenation refining reaction pressure was 0.7 MPa, and the volume hourly space velocity (VHSV) was 2 h⁻¹. -1 The catalyst was evaluated through a 1500-hour long-term operation.

[0066] The comparative evaluation results of the caprolactam hydrogenation refining catalysts A2 and B3 after 1500 hours of operation are shown in Figures 1 and 2. The evaluation results show that the PAN value of catalyst A2 after hydrogenation refining caprolactam is consistently lower than that of catalyst B3; however, the PM value of catalyst A2 after hydrogenation refining caprolactam is consistently higher than that of catalyst B3. Therefore, the hydrogenation effect of catalyst A2 is superior to that of catalyst B3.

[0067] The strengths of caprolactam hydrogenation refining catalysts A2 and B3, which had been running for 1500 hours, were tested. The test results are shown in [the table below]. Figure 5 (Comparison of the strength of catalysts A2 and B3).

[0068] from Figure 5 The strength test results show that the strength change of catalyst A2 before and after the hydrogenation reaction is not significant, proving that the catalyst structure of the present invention has good stability. However, the strength of catalyst B3 before and after the hydrogenation reaction is very different. After running for 1500 hours, the catalyst strength drops significantly. After being washed by caprolactam for a long time, the catalyst structure becomes brittle and has poor structural stability, which affects the service life and performance of the catalyst.

[0069] Based on the above hydrorefining experimental results, compared with the existing B3 catalyst, the A2 catalyst of the present invention has suitable specific surface area, pore volume and strength, thus exhibiting good hydrogenation activity, selectivity and structural stability in the hydrorefining of caprolactam. Moreover, the catalyst is used in a fixed-bed reactor, which is convenient for loading and unloading operations and easy to industrialize.

[0070] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements or substitutions without departing from the principles of the present invention, and these improvements or substitutions should also be considered within the scope of protection of the present invention.

Claims

1. A catalyst for the hydrogenation refining of caprolactam, characterized in that, The catalyst, by weight percentage, comprises 20-30% nickel oxide, 3-10% molybdenum oxide, 2-10% chromium oxide, 45-75% alumina, and 1-5% additives. It has a specific surface area of ​​180-260 m² / g, a pore volume of 0.45-0.65 cm³ / g, a bulk density of 0.65-0.75 g / ml, and a strength of 180-210 N / cm. This supported catalyst, prepared by a co-precipitation-impregnation method, is used in a fixed-bed reactor. The supported catalyst consists of a support, an active component, and additives. The support includes alumina and chromium oxide, the active component includes nickel oxide and molybdenum oxide, and the additives include one or two rare earth metals and transition metals.

2. The caprolactam hydrogenation refining catalyst according to claim 1, characterized in that: The rare earth metal is one or both of lanthanum and cerium; the transition metal is one or both of titanium and zirconium.

3. A method for preparing a catalyst for the hydrogenation refining of caprolactam, characterized in that: A method for preparing a caprolactam hydrogenation refining catalyst according to claim 1 or 2. Includes the following steps: S0: Provide a first mixture containing aluminum and chromium, a second mixture containing an additive, and a third mixture containing nickel and molybdenum; S1: Dissolve the precipitant to prepare a solution, then add the first and second mixtures to the precipitant solution by parallel-flow dropwise addition and stir to react, obtaining a uniform precipitate. The pH value is strictly controlled during the parallel-flow dropwise addition process. After precipitation is completed, stirring is stopped and aging begins. After aging is completed, the mixture is filtered, washed, dried, and calcined to obtain modified catalyst powder. After adding molding aids and pore-forming agents to the catalyst powder, the mixture is kneaded, extruded, dried, and calcined to obtain a modified catalyst support; S2: The thoroughly dissolved third mixture is impregnated onto the above-molded catalyst support, aged at room temperature for 3-5 hours, dried at 100-130 degrees Celsius for 4-6 hours, and finally calcined at 300-500 degrees Celsius for 4-6 hours to obtain the caprolactam hydrogenation refining catalyst.

4. The method for preparing a caprolactam hydrogenation refining catalyst according to claim 3, characterized in that: The step of co-precipitating the first mixture and the second mixture to obtain a catalyst support containing an auxiliary agent includes: S11: Dissolving the precipitant completely to prepare a solution of a certain concentration, then slowly adding the first mixture and the second mixture to the precipitant solution by parallel dripping and stirring. The pH of the solution is strictly controlled to be 7-9 during the dripping process; S12: After the two mixtures have been added and precipitation is complete, stirring is stopped and aging begins. The aging time is 4-8 hours. After aging, the precipitate is washed with deionized water with a conductivity of <5 μS / cm. The washing is stopped when the conductivity of the washed water is <100 μS / cm. The solid precipitate is dried at 100-120℃ for 2-6 hours to obtain a composite basic salt precursor. Then, it is calcined at 500-800℃ in air for 4-6 hours to obtain a modified catalyst powder; S13: The catalyst powder, binder, plasticizer, pore-forming agent, etc. are kneaded in a certain proportion and extruded into strips. The extruded strips are shaped into φ1.5mm*(3-8)mm. The clover-shaped catalyst support was then dried at 100–120°C for 4–6 hours to ensure that the moisture content of the support was <3%, and then calcined at 700–900°C for 3–6 hours to obtain the modified catalyst support.

5. The method for preparing a caprolactam hydrogenation refining catalyst according to claim 3, characterized in that: The precipitant is one or more of ammonium carbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, and potassium bicarbonate.

6. The application of the caprolactam hydrogenation refining catalyst according to claim 1 or 2, characterized in that: This method is applied to the hydrogenation refining of caprolactam in a fixed-bed reactor. The fixed-bed reactor is packed with the caprolactam hydrogenation refining catalyst, and hydrogen gas and crude caprolactam solution are simultaneously introduced at a certain hydrogen-to-liquid ratio for hydrogenation refining. The caprolactam accounts for 25-55% of the solution by mass, the molar ratio of hydrogen gas to caprolactam aqueous solution is (2-4):1, the hydrogenation refining temperature is 50-70℃, the hydrogenation refining pressure is 0.5-1.0 MPa, and the volumetric hourly space velocity is 1-3 h⁻¹. -1 .

Citation Information

Patent Citations

  • Method for hydrofining caprolactam in magnetically stabilized bed

    CN102050783A

  • Method for refining caprolactam through fixed-bed hydrogenation

    CN103086968A

  • Caprolactam hydrofining catalyst and method

    CN106140195A

  • Hydrogenation catalyst for refining of caprolactam and preparation method thereof

    CN109453780A

  • Preparation method of caprolactam hydrofining catalyst, caprolactam hydrofining catalyst and method for refining caprolactam by using caprolactam hydrofining catalyst

    CN112221504A